Stalk cell polar ion transport provide for bladder‐based salinity tolerance in Chenopodium quinoa. Issue 5 (1st June 2022) - Bazihizina, Nadia; Böhm, Jennifer; Messerer, Maxim; Stigloher, Christian; Müller, Heike M.; Cuin, Tracey Ann; Maierhofer, Tobias; Cabot, Joan; Mayer, Klaus F. X.; Fella, Christian; Huang, Shouguang; Al‐Rasheid, Khaled A. S.; et al.
Summary: Chenopodium quinoa uses epidermal bladder cells (EBCs) to sequester excess salt. Each EBC complex consists of a leaf epidermal cell, a stalk cell, and the bladder. Under salt stress, sodium (Na + ), chloride (Cl − ), potassium (K + ) and various metabolites are shuttled from the leaf lamina to the bladders. Stalk cells operate as both a selectivity filter and a flux controller. In line with the nature of a transfer cell, advanced transmission electron tomography, electrophysiology, and fluorescent tracer flux studies revealed the stalk cell's polar organization and bladder‐directed solute flow. RNA sequencing and cluster analysis revealed the gene expression profiles of the stalk cells. Among the stalk cell enriched genes, ion channels and carriers as well as sugar transporters were most pronounced. Based on their electrophysiological fingerprint and thermodynamic considerations, a model for stalk cell transcellular transport was derived.